EARLY DETECTION OF CHILDREN WITH SPECIAL NEEDS EARLY CHILDHOOD EDUCATION - Septiyani Endang Yunitasari; Yuyun Tri Kaeksi; Yanti Komala; Roudotul Janah; Ni Putu Dessy Ari Susanti; Epah Maspupah; Siti Rahayu (International Conferences on Early Childhood Education Proceedings, 2024)
Children with special needs also need special attention in the early stages of their development. These children may face various challenges, such as developmental disorders, autism, hearing impairment, or other health issues that require appropriate attention and intervention. This research is a qualitative research with document study data research method. The results show that early detection in early childhood education is an important first step to providing inclusive and equitable education. It involves recognizing a child's special characteristics or needs early on to provide timely interventions. Early detection is important for children with a range of special needs such as autism, speech impairment, hearing impairment, and emotional and social problems. The role of teachers and parents in early detection is crucial, with strong collaboration and support. An inclusive approach to early childhood education is key to creating an environment that embraces diversity and allows all children to develop to their potential. With awareness, training and strong collaboration, inclusive approaches can help create a more inclusive and equitable future for all children.